The Roles, Opportunities, and Challenges of PAI Teacher's Leadership in Senior High Schools - Sholihah, Hidayatus; Syukur, Fatah; Ismail, Ismail; Rosyid, Ahmad Zaenur; Amantai, Khajyet (IAIN Ponorogo, 2024)
This research aims to explore the role of PAI teacher leaders in leading students to achieve their best achievements, opportunities and challenges for them to become PAI teacher leaders. The researchers used interviews, documentation, and observations to collect data. This qualitative research was conducted at several State High Schools in Central Java. They were SMAN 3 Semarang, SMAN 1 Demak, SMKN 4 Kendal, and SMKN 1 Salatiga. The data analysis model used by the researchers was the interactive model of Miles, Huberman, and Saldana. It involved data condensation, data display, and conclusion drawings. The research results show that PAI teacher leaders in several high schools play a role in leading their students to achieve the best achievements in student competitions. Apart from that, PAI teacher leaders have the opportunity to develop their leadership abilities if they are supported by a school principal who distributes his leadership roles well and has a democratic leadership style in leading the school so that teachers are involved in decision-making.